A Framework for Maintenance and Scaling of an Evidence-based Guideline Program. Issue 2 (March 2019) - Seneski, Annie; Stack, Anne M.
Abstract : Introduction: Use of Evidence-based Guidelines (EBGs) has been shown to improve and standardize care. After implementation and maturation of a guideline program, next steps include incorporating new evidence, sustaining adherence, minimizing measurement burden and fostering scaling of the program. We propose a framework for maintenance and dissemination of an EBG program. Methods: Using a program of 28 EBGs developed for use in a pediatric emergency department (ED) in 2010, we developed: a framework for iterative review and revision, a strategy to measure ongoing use in practice and an approach for minimizing repeated measurement sufficient to evaluate outcomes. Also, we created a process to spread the EBG program to the hospital's Department of Pediatrics. Results: The framework for maintenance and spread of a program of EBGs resulted in an annual review of individual guidelines with 14 revisions warranted by new evidence, some leading to decreased medication utilization and hospitalization rates. We demonstrated adherence to key quality measures, and decreased the number of measures from 89 to 43, retiring 46 measures with stable peformance. We spread the process for program development to the hospital pediatric department resulting in 36 new EBGs. Conclusions: We developed a framework for maintenance and scale of a program of EBGs. Our key learning points were that regular incorporation of new evidence, assessment and feedback on performance and leadership with administrative support are necessary to maintain improvement. This framework may assure sustainability and inform other guideline programs. We offer processes to promote guideline dissemination within an academic hospital.